Emerging coronaviruses: Genome structure, replication, and pathogenesis - Chen, Yu (J Med Virol, 2020)
The recent emergence of a novel coronavirus (2019‐nCoV), which is causing an outbreak of unusual viral pneumonia in patients in Wuhan, a central city in China, is another warning of the risk of CoVs posed to public health. In this minireview, we provide a brief introduction of the general features of CoVs and describe diseases caused by different CoVs in humans and animals. This review will help understand the biology and potential risk of CoVs that exist in richness in wildlife such as bats.